People's perception in Early Warning System: a case study of Bhandara VDC Padariya-7 in Chitwan district, Nepal - Lamichhane, Richa (BRAC University, 2012)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2011.